Adaptive sliding mode control method for DC–DC converters. Issue 9 (1st September 2015) - Shen, Liqun; Lu, Dylan Dah‐Chuan; Li, Chengwei
Abstract : This study presents an adaptive sliding mode control method for DC–DC converters. In the state space model of DC–DC converters, there are always some unknown coordinate components of the desired equilibrium point (static working point), which are necessary to obtain the error vector and then build the sliding surface. To obtain the unknown coordinate components of the equilibrium point, an adaptive law is proposed. The adaptive law and the error response are formulated in a single equation, which determines the system performance. A systematic sliding mode control design procedure of a class of DC–DC converters is hence carried out. To verify the usefulness and effectiveness of the proposed adaptive sliding mode control method, the negative output elementary super lift Luo converter is used as a design example. Simulation and experimental results are reported to confirm the proposed approach.